Analisis Unsur Fisik dan Unsur Batin pada Puisi Aku Menemuimu Di Ujung Malam, Maqamat Cinta, Bersamamu Ketika Senja dan Bersama Syair Kenangan Karya Heri Isnaini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Heri Isnaini's poetic works offer a profound beauty of language and meaning that needs to be analyzed. The purpose of this research is to analyze the physical and mental elements contained in the poem by Heri Isnaini entitled